Dreamweaver MX 2004 - McFarland, David Sawyer (Missing manual., 2004)
Macromedia's Dreamweaver MX 2004 offers a rich environment for building professional web sites, with drag-and-drop simplicity, clean HTML code, and dynamic database-driven web site creation tools. It comes with everything except perhaps the most important feature of all: a printed manual. Enter Dreamweaver MX 2004: The Missing Manual, the book that enables both first-time and experienced web designers to bring stunning, interactive web sites to life. What sets this new edition apart is the crystal-clear writing, welcome humor, and exclusive features like these: